Formation of wear–resistant chromium–vanadium cast iron coating using a continuous and pulsed electron beam; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Tatarkina N. V.; Ziganshin A. I.; Dampilon B. V. Bair Vyacheslavovich; Durakov V. G.; Tolstokulakov A. M. (2014, 2014)
Title screen